THE EFFECT OF PRICE AND SERVICE QUALITY ON CUSTOMER SATISFACTION OF GOJEK USERS - Pratama, M Aditiya; Kusumastuti, Ratih (UIN Sunan Gunung Djati Bandung, 2024)
This study aims to investigate the effect of price and service quality on customer satisfaction of Gojek service users in Jambi City. In a modern society that is increasingly adopting technology, Gojek as an online transportation service provider offers a variety of products and services, leading the market in Indonesia. This study involved 50 students majoring in accounting from Jambi University who often use Gojek services. This research method adopts an associative research approach with analysis involving validity, reliability, normality, multicollinearity, and heteroscedasticity tests, as well as multiple linear regression analysis with SPSS version 23. The results showed that price and service quality have a significant influence on Gojek customer satisfaction. Price and service quality are positive, indicating the importance of setting the right price and improving service quality in increasing customer satisfaction. The coefficient of determination is 82.7%, indicating the model can explain variations in customer satisfaction. A flexible pricing strategy and improved service quality can strengthen relationships with customers and maintain competitiveness in the online transportation service market. By understanding the factors that influence customer satisfaction, companies can continuously improve their services according to local customer expectations and needs.